IMMUNOSTIMULATING EFFECT OF AQUEOUS EXTRACT OF AMPHYPTERYGIUM ADSTRINGENS ON IMMUNE CELLULAR RESPONSE IN IMMUNOSUPPRESSED MICE. - RamÃrez-León, Adriana; Barajas-Martinez, Héctor; Flores-Torales, Edgardo; Orozco-Barocio, Arturo (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Amphypterygium adstringens is a Mexican tree known as cuachalalate whose bark is habitually used for the treatment of fresh wounds, gastric ulcers, gastrointestinal cancer and various inflammatory conditions. The aim of this study was to evaluate the immunostimulant effect of the aqueous extract of A. adstringens on immune cellular response in immunosuppressed mice. An aqueous extract from the bark of cuachalalate was administered into BALB/c mice for 10 days. We assessed their immunostimmulant activity on cellular immune response by Delayed Type Hypersensitivity Response (DHT) to dinitrofluorobencene (DNFB) and by MTT assay. L5178Y lymphoma was used as immunossuppression model. An increase in DHT was observed after treatment with 10 and 100 mg/kg of the aqueous extract from A. adstringens oral treatment in lymphoma bearing mice. Splenocyte proliferation rate was significantly increased (2.5 time) in immunosuppresed mice treated with 10 mg/kg oral treatment compared with group that received vehicle only. The present study showed for the first time the aqueous extract from A. adstringens as a positive immunostimulant agent in lymphoma bearing mice and we demonstrated evidence to support the traditionally use of cuachalalate in conditions in which the immune system is depressed.